Pengaruh Orientasi Etika terhadap Independensi dan Kualitas Audit Auditor BPK-RI - Akhmad Samsul Ulum (Journal of Accounting and Investment, 2005)
The research is to test the effects of internal factors within an auditor of BPK (ethical orientation: idealism relativism) on independence in fact and audit quality. Respondents of the research are BPK auditors across Indonesia. The method used in the research is  cluster sampling method. The research uses path analysis approach in order to test the effects of idealism and relativism on independence and audit quality. Analysis was conducted on 115 questionnaires and showing empirical evidences that idealism affects positively and relativism affects negatively the independence in fact of BPK auditors. Idealism did not directly affect the audit quality, but by means of intervening variables, i.e., independece in fact functioning as a mediator between idealism variables and audit quality. Relativism directly affects the quality audits of BPK auditors. Results of the research also showing that independence in fact positively affects audit quality of the BPK auditors.